The effects of acute renal denervation on kidney perfusion and metabolism in experimental septic shock - Post, Emiel Hendrik (BMC Nephrol, 2017)
BACKGROUND: Perfusion deficits likely play an important role in the development of renal dysfunction in sepsis. Renal denervation may improve kidney perfusion and metabolism. METHODS: We randomized 14 female sheep to undergo bilateral surgical renal denervation (n = 7) or sham procedure (n = 7) prior to induction of sepsis. Renal blood flow (RBF) was measured with a pre-calibrated flowprobe. Laser Doppler probes were implanted to measure cortical and medullary perfusion. Cortical glucose, lactate and pyruvate levels were measured using the microdialysis technique. Creatinine clearance was determined. Sepsis was induced by peritonitis and fluid resuscitation was provided to avoid hypovolemia. RESULTS: RBF and cortical perfusion were higher in the denervated group during the first 6 h after induction of sepsis (P < 0.001 and P < 0.05, respectively), while medullary perfusion decreased similarly in both groups. After hypotension developed, RBF decreased to similar levels in both groups. Cortical pyruvate and lactate levels were lower in the denervated animals (P < 0.001 and P < 0.001, respectively). There were no differences between groups in creatinine clearance, urine output or time to oliguria. CONCLUSION: Denervation thus caused an early increase in RBF that was distributed towards the kidney cortex. Although associated with an attenuation of early cortical metabolic alterations, denervation failed to prevent the deterioration in renal function.